Hydrogen Bond-Induced Activation of Photocatalytic and Piezophotocatalytic Properties in Calcium Nitrate Doped Electrospun PVDF Fibers - Orudzhev, F F; Sobola, D S; Ramazanov, Sh M; Častková, K; Selimov, D A; Rabadanova, A A; Shuaibov, A O; Gulakhmedov, R R; Abdurakhmanov, M G; Giraev, K M (Polymers, 2023)
In this study, polyvinylidene fluoride (PVDF) fibers doped with hydrated calcium nitrate were prepared using electrospinning. The samples were analyzed using scanning electron microscopy (SEM), X-ray diffraction (XRD), optical spectroscopy, X-ray photoelectron spectroscopy (XPS), Fourier transform infrared (FTIR), Raman, and photoluminescence (PL) spectroscopy. The results are complementary and confirm the presence of chemical hydrogen bonding between the polymer and the dopant. Additionally, there was a significant increase in the proportion of the electroactive polar beta phase from 72 to 86%. It was shown that hydrogen bonds acted as a transport pathway for electron capture by the conjugated salt, leading to more than a three-fold quenching of photoluminescence. Furthermore, the optical bandgap of the composite material narrowed to the range of visible light energies. For the first time, it the addition of the salt reduced the energy of the PVDF exciton by a factor of 17.3, initiating photocatalytic activity. The calcium nitrate-doped PVDF exhibited high photocatalytic activity in the degradation of methylene blue (MB) under both UV and visible light (89 and 44%, respectively). The reaction rate increased by a factor of 2.4 under UV and 3.3 under visible light during piezophotocatalysis. The catalysis experiments proved the efficiency of the membrane design and mechanisms of catalysis are suggested. This study offers insight into the nature of chemical bonds in piezopolymer composites and potential opportunities for their use.
Keywords: exciton; salt; photocatalysis; piezophocatalysis; PVDF; visible light; hydrogen bond